FORMULATION AND EVALUATION OF GASTRO RETENTIVE DRUG DELIVERY SYSTEM OF ZANAMIVIR USING DIFFERENT POLYMERS - Kumar, V. Vijaya; Gladiola, B. Deekshi; Chetty, C. Madhusudhana; Ugandar, R. E. (Journal of Biomedical and Pharmaceutical Research, 2019)
The objective of the present study is to develop gastro retentive drug delivery system of Zanamivir .Floating tablets of Zanamivir were developed with a gas generating agent NaHCO3 and in combination of different hydrophobic and hydrophilic polymers like xanthan gum, guar gum, HPMC and methyl cellulose .In the present work attempts have been made to prepare six formulations of Zanamivir in different ratios of drug and polymer to get a desired release profile by direct compression method .All the prepared tablets were evaluated in terms of pre compression and post compression parameters. FTIR studies revealed the absence of drug polymer interactions .Among all the formulations F5 Showed 97.4% of in vitro drug release for 10 hours and hence formulation F5 is selected as an optimized formulation. The optimized formulation F5 was found to follow Higuchi release kinetics and zero order. Further formulation F5 was subjected to accelerated stability studies for 3 months. It showed that the optimized formulation was intact without any interactions. Finally the optimized formulation F5 complying with all properties of floating tablets was found to be satisfactoryKeywords: Zanamivir, floating tablet, natural gums, sodium bicarbonate, gastro retentive drug delivery systems